English Medium Instruction and the Internationalization of Higher Education in Latin America: A Case Study from a Colombian University - Isabel Tejada-Sanchez; Mario Molina-Naar (Universidad de La Sabana, 2021)
This study discusses the implementation of English medium instruction (EMI) at a Colombian university. First, the paper reviews the rise of EMI in the internationalization of higher education. Second, it illustrates how one university incorporated EMI as part of an internationalization process. Third, it identifies the perceptions that a group of administrators, faculty, and students have regarding the EMI initiative. Questionnaires, semi-structured interviews, and document analysis were conducted. Findings suggest that EMI is tied to the structuring of an internationalization office, curricular reforms, and English language learning support. Participants' perceptions are associated with their imaginaries, identities, experiences, and obligations in relation to the English language. The study concludes that the implementation of EMI within the internationalization of universities is inevitable, yet a sustainable EMI strategy requires contextual awareness and articulation amongst its participants. Received: 28/02/2020 Accepted: 18/09/2020